2015
DOI: 10.1038/pr.2015.51
|View full text |Cite
|
Sign up to set email alerts
|

A possible link between early probiotic intervention and the risk of neuropsychiatric disorders later in childhood: a randomized trial

Abstract: Background: Recent experimental evidence suggests that gut microbiota may alter function within the nervous system providing new insight on the mechanism of neuropsychiatric disorders. Methods: Seventy-five infants who were randomized to receive Lactobacillus rhamnosus GG (ATCC 53103) or placebo during the first 6 mo of life were followed-up for 13 y. Gut microbiota was assessed at the age of 3 wk, 3, 6, 12, 18, 24 mo, and 13 y using fluorescein in situ hybridization (FISH) and qPCR, and indirectly by determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
205
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(210 citation statements)
references
References 35 publications
2
205
1
2
Order By: Relevance
“…The effect of the synbiotic intervention in the study cohort is only minor and does not explain the elevated levels, as similar effect was detected in both intervention groups-even during the intervention the bifidobacteria levels were not different between the groups. The observed elevated bifidobacterial levels in early life are potentially beneficial as previous reports suggest a protective role of bifidobacteria against excessive weight gain and neuropsychiatric disorders in later life (Kalliomäki et al, 2008;Pärtty et al, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…The effect of the synbiotic intervention in the study cohort is only minor and does not explain the elevated levels, as similar effect was detected in both intervention groups-even during the intervention the bifidobacteria levels were not different between the groups. The observed elevated bifidobacterial levels in early life are potentially beneficial as previous reports suggest a protective role of bifidobacteria against excessive weight gain and neuropsychiatric disorders in later life (Kalliomäki et al, 2008;Pärtty et al, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…In one study, infants were given either Lactobacillus rhamnosus GG or placebo during the first 6 months of life and gut microbiota was assessed over a period of 13 years. The study found a correlation between lower counts of Bifidobacterium species and development of ADHD or Asperger’s Syndrome (Partty, Kalliomaki, Wacklin, Salminen, & Isolauri, 2015). …”
Section: The Gut Microbiomementioning
confidence: 93%
“…Social deficits in mice (less interest in social interaction, poor memory for social partners) [110,113] Reversal of social deficits in murine models of ASD [111,115] Reversal of antibiotic-induced social deficits in mice [113] Reduced risk for ASD [116] , reduced symptom severity in children with ASD (open pilot) [117] Transplant of standardized human gut microbiota to children with ASD improved ASD symptoms in open-label pilot [118] Pain Visceral hypersensitivity in mice [119] Visceral hypersensitivity in healthy mice [94,120,135] Reversal of visceral hypersensitivity in stressed mice [122] Increased risk for IBS in humans [51] Positive effects on pain in IBS patients [127] Reversal of stressinduced visceral hypersensitivity in rats [121] Reversal of antibiotic-induced visceral hypersensitivity in mice [135] Positive effects on IBS symptoms in humans [127] Transplant from IBS donors increases GI symptoms (accelerated gastrointestinal transit, increased intestinal permeability) in mice [125,126] Transplant from healthy donors reduces GI symptoms (constipation, diarrhea, indigestion, abdominal pain) in children with ASD (open-label pilot) [118] www.advancedsciencenews.com www.bioessays-journal.com been several studies reporting no effect of probiotics on these measures, [99] these disparate results may be explained by straindependent effects or a moderating effect of symptom severity because it has been reported that the beneficial effects are greatest for those with the most negative symptoms at baseline. [100] …”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
“…Individuals with ASD often exhibit gastrointestinal problems and alterations in the microbiota. [115] Accordingly, preliminary pilot studies show that probiotics may reduce risk for ASD onset if administered perinatally [116] and reduce symptom severity in children already diagnosed with ASD. [117] In addition, significant improvements in gastrointestinal and behavioral symptoms were observed in an open pilot of faecal microbiota transplants for children with ASD.…”
Section: Microbiota Is Critical For Social Behaviormentioning
confidence: 99%